Genetic predictions of life expectancy in southern Thai patients with β0 ‑thalassemia/Hb E. Issue 6 (2022) - Nuinoon, Manit; Rattanaporn, Patchara; Benjchareonwong, Thongchai; Choowet, Anuchit; Suwanno, Komsai; Saekoo, Ngamta; Lekpetch, Krongjit; Thipthara, Orapan; Svasti, Saovaros; Fucharoen, Suthat
No abstract available